Running Event “Trackpresso: 5K Color Run 2024 di Kota Semarang, Jawa Tengah” sebagai Event Manager dan Sponsorship Manager - Rahmanuz Zidan, Aimar; Naryoso, Agus; Manalu, S. Rouli (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
This project focuses on the comprehensive preparation and execution of the Trackpresso: 5k Color Run 2024 event. Anak Panah Kopi, as the client, collaborated with the project team due to a desire to create an event that aligned with recent popular trends. This project report is based on the event management framework outlined in Joe Goldblatt's book